Knowing Art
XXIV, 167 p.
Keywords: Artworks potentially convey two kinds of knowledge. They obviously afford knowledge of art itself, and they also afford general empirical knowledge, especially knowledge of human psychology and value. Knowing Art collects ten original essays written by leading philosophers who distill and build upon recent work at the intersection of aesthetics and epistemology. Specific topics addressed include the objectivity of critical knowledge, the quality of critical testimony, the roles of principles and perception in critical reasoning, phenomenal knowledge of what a work of art is like, the acquisition of factual information and psychological understanding from fictions, and the limits of images as sources of historical evidence. In addressing these topics, the volume also explores the challenges that art poses for theories of knowledge as well as the challenges that artistic knowledge poses to traditional views about art.